Emerging roles of AATF: Checkpoint signaling and beyond. Issue 5 (4th November 2020) - Srinivas, Akshatha N.; Suresh, Diwakar; Mirshahi, Faridoddin; Santhekadur, Prasanna K.; Sanyal, Arun J.; Kumar, Divya P.
Abstract: Apoptosis antagonizing transcription factor (AATF), an interacting partner of RNA polymerase II is a multifunctional protein that is highly conserved in eukaryotes. In addition to the regulation of gene expression as a transcriptional coactivator, AATF is shown to play a dual role in regulating the cell cycle by displacing histone deacetylases 1 (HDAC1) from the retinoblastoma‐E2F transcription factor (Rb‐E2F) complex and also from the specificity protein 1 (Sp1) transcription factor responsible for p21 expression, thereby ensuring cell proliferation and growth arrest, respectively, at different checkpoints of the cell cycle. Notably, AATF has emerged as one of the most important modulators of various cellular responses such as proliferation, apoptosis, and survival. Studies have demonstrated that AATF protects cells from multiple stress stimuli such as DNA damage, ER stress, hypoxia, or glucose deprivation by inducing cell cycle arrest, autophagy, or apoptosis inhibition. Furthermore, AATF serves as a critical regulator in various cancers and promotes tumorigenesis by protecting cancer cells from apoptosis induction, favoring cell proliferation, or promoting cell survival by autophagy. Recent studies have demonstrated the key role of AATF in ribosome biosynthesis and have also provided insights into the mechanistic role of AATF, offering impressive cytoprotection in myocardial infarction, neurologic diseases, and nephronophthisis. In this review, we will provide a comprehensive overview of the role of AATF and shed light on its emerging roles underlining the potential use of AATF as a novel biomarker and as an effective therapeutic target. Abstract : Apoptosis antagonizing transcription factor (AATF), an interacting partner of RNA polymerase II is a multifunctional protein that is highly conserved in eukaryotes. Notably, AATF has emerged as one of the most important modulators of various cellular responses such as proliferation, apoptosis, and survival. In this review, we will provide a comprehensive overview of the role of AATF and shed light on its emerging roles underlining the potential use of AATF as a novel biomarker and as an effective therapeutic target.